Chain pain following cardiac surgery in a 35-year-old man. Issue 3 (18th August 2018) - Marchandot, Benjamin; Radulescu, Bogdan; Morel, Olivier
Abstract : Clinical introduction: A 35-year-old man with multiple cardiovascular risk factors presented with a recent history of fever and acute heart failure. His initial echocardiogram showed evidence of severe aortic regurgitation due to ongoing infective endocarditis. Preoperative coronary angiography revealed no coronary abnormalities. Urgent aortic valve replacement was performed and a 29 mm St Jude mechanical valve was implanted. While blood and resected valvular tissue cultures were negative for bacteria, a PCR-based analysis revealed the presence of penicillin-sensitive Streptococcus pneumoniae . Echocardiographic follow-up study at day 3 showed excellent mechanical valve function with no persistent signs of endocarditis. Eight days after surgery, our patient presented with severe chest pain. The ECG is shown in figure 1A and coronary angiography was performed for diagnostic confirmation (figure 1B–D and online supplementary video 1 ). Question: Which of the following is most likely the diagnostic? Occlusion of the left anterior descending coronary artery Dissection of the left anterior descending coronary artery Valsalva aneurysm presenting as an acute coronary syndrome Left anterior descending coronary artery spasm Left main coronary aneurysm